Measuring the Justice of Children's Inheritance Rights in Polygamy: A Comparison between Legal and Siri Marriages from the Perspective of Islamic Law - Sri Wulandari; Achmad Kholiq; Aan Jaelani; Adang Djumhur Djumhur (Faculty of Law, Universitas Pekalongan, 2025)
The phenomenon of polygamy in Indonesia is still part of the complex socio-religious reality, mainly when polygamy is carried out without official registration, or known as nikah siri. In practice, the unrecorded marriage has a profound impact on the legal protection of children, particularly in terms of inheritance rights. Children born from serial marriages often do not receive legal recognition, so their position as heirs becomes weak or is not recognized at all. This study aims to measure the justice of children's inheritance rights in the context of polygamy through a comparison between children from formal and serial marriages in the perspective of Islamic law. With a normative qualitative approach, this study employs an in-depth literature review method, drawing on Islamic legal sources (the Qur'an, hadith, and fiqh books), national laws and regulations (Law No. 1 of 1974, Compilation of Islamic Law), as well as jurisprudence documents and other relevant scientific literature. The results of the study show that in Islamic fiqh, the principle of justice entitles all children from a valid marriage, whether recorded or not, according to shari'a, to inheritance as long as their fate is clear.However, in Indonesian national law, marriage registration is a mandatory administrative requirement to recognize the validity of the legal relationship between spouses, including in terms of inheritance. Children from a nikah siri do not automatically obtain inheritance rights unless the isbat nikah is determined and the determination of nasab is carried out through the court. This inequality highlights the disparity between the principles of Islamic law and the positivism of national law. This study recommends updating the regulations and approach of maqāṣid al-syarī'ah in family law policy to ensure justice and nondiscrimination of children's rights in all forms of marriage.